Clinical picture of heparin-induced thrombocytopenia (HIT) and its differentiation from non-HIT thrombocytopenia - Warkentin, Theodore E. (Thrombosis and Haemostasis, 2016)
HIT is an acquired antibody-mediated disorder strongly associated with thrombosis, including microthrombosis secondary to disseminated intravascular dissemination (DIC). The clinical features of HIT are reviewed from the perspective of the 4Ts scoring system for HIT, which emphasises its characteristic timing of onset of thrombocytopenia. HIT antibodies recognize multimolecular complexes of platelet factor 4 (PF4)/heparin. However, a subset of HIT sera recognise PF4 bound to platelet chondroitin sulfate; these antibodies activate platelets in vitro and in vivo even in the absence of heparin, thus explaining: delayed-onset HIT (where HIT begins or worsens after stopping heparin); persisting HIT (where HIT takes several weeks to recover); spontaneous HIT syndrome (a disorder clinically and serologically resembling HIT but without proximate heparin exposure); and fondaparinux-associated HIT (four distinct syndromes featuring thrombocytopenia that begins or worsens during treatment with fondaparinux), with a new patient case presented with ongoing thrombocytopenia (and fatal haemorrhage) during treatment of HIT with fondaparinux, with fondaparinux-dependent platelet activation induced by patient serum (“fondaparinux cross-reactivity”). Ironically, despite existence of fondaparinux-associated HIT, this pentasaccharide anticoagulant is a frequent treatment for HIT (including one used by the author). HIT can be confused with other disorders, including those with a) timing similar to HIT (e. g. abciximab-associated thrombocytopenia of delayed-onset); b) combined thrombocytopenia/thrombosis (e. g. symmetrical peripheral gangrene secondary to acute DIC and shock liver); and c) both timing of onset and thrombosis (e. g. warfarin-associated venous limb gangrene complicating cancer-associated DIC). By understanding clinical and pathophysiological similarities and differences between HIT and non-HIT mimicking disorders, the clinician is better able to make the correct diagnosis.
Keywords: Heparin-induced thrombocytopenia; platelet activation; thrombosis